Network Traffic Prediction Based on Time Series Modeling - AlSaleem, Naors Y. Anad (Iraqi Journal of Science, 2023)
Predicting the network traffic of web pages is one of the areas that has increased focus in recent years. Modeling traffic helps find strategies for distributing network loads, identifying user behaviors and malicious traffic, and predicting future trends. Many statistical and intelligent methods have been studied to predict web traffic using time series of network traffic. In this paper, the use of machine learning algorithms to model Wikipedia traffic using Google’s time series dataset is studied. Two data sets were used for time series, data generalization, building a set of machine learning models (XGboost, Logistic Regression, Linear Regression, and Random Forest), and comparing the performance of the models using (SMAPE) and (MAPE). The results showed the possibility of modeling the network traffic time series and that the performance of the linear regression model is the best compared to the rest of the models for both series.